OUTDOOR GAMES IN THE SYSTEM OF PHYSICAL EDUCATION AT THE UNIVERSITY (Conferencea, 2023)
The use of outdoor games in physical education classes at the university allows students to become involved in a healthy lifestyle, stimulate motivation to play sports, cultivate important psychophysical and personal qualities, increase the effectiveness of the physical education process at the university.